Development of Picture Card Media Based on Differentiated Learning Design to Improve Indonesian Speaking Skills of Grade I Students of Riyadh Indonesian School - Ariyani, Rina; Sukartiningsih, Wahyu; Istiq'faroh, Nurul (Papanda Publisher, 2025)
This study aims to develop an image card-based learning media using a differentiated learning design to improve the speaking skills of first-grade students at Sekolah Indonesia Riyadh. The research adopted the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media consists of image cards with various themes supporting speaking skill development, such as recognizing objects, naming colors, and role-playing. The research employed a Research and Development (R&D) method with a pretest-posttest design to measure the improvement in students' speaking abilities before and after the intervention. A total of 20 first-grade students participated in the study, consisting of an equal number of boys and girls aged 6–7 years. The development results show that this learning media has a very high validity with a score of 86.66%, which falls under the very valid category based on assessments from media and content experts. The practicality of the media received excellent feedback, with a 100% rating from teachers indicating that it is easy to use and effective in the learning process. The effectiveness of this media was measured by the improvement in pretest and posttest scores, with the average pretest score of 54.7, while the posttest score increased to 85.0, with an N-Gain of 0.80, indicating very effective results. However, the study was limited to a small sample within a single school, which may affect the generalizability of the findings. Based on these findings, it can be concluded that the image card-based learning media with a differentiated learning design is proven to be valid, practical, and effective in enhancing the speaking skills of first-grade students at Sekolah Indonesia Riyadh. Therefore, the use of this media can be applied more broadly in other classrooms to support the optimal development of students' speaking skills.